A Case Study of an Evaluation of Pen-and-Paper Homework and Project-Based Learning of Statistical Literacy in an Introductory Statistics Course - Kristin Lilly; Basil M. Conway (Journal of Statistics and Data Science Education)
Pen-and-paper homework and project-based learning are both commonly used instructional methods in introductory statistics courses. However, there have been few studies comparing these two methods exclusively. In this case study, each was utilized in two different sections of the same introductory statistics course at a regional state university. Students’ statistical literacy was measured by exam scores across the course, including the final. The comparison of the two instructional methods includes using descriptive statistics and two-sample t-tests, as well authors’ reflections on the instructional methods. Results indicated that there is no statistically discernible difference between the two instructional methods in the introductory statistics course.